Comparison on economic and technical analysis for fertilizer mechanization application affecting oil palm production / Lokmannurhakim Muhamad Yusop - Muhamad Yusop, Lokmannurhakim (Faculty of Plantation and Agrotechnology, 2019)
The Malaysian palm oil industry business keeps on making a noteworthy commitment to the national economy towards Gross Domestic Product (GDP) with the contribution of about 5% to 7% every year. As in 2017, the contribution toward Gross Nation Income (GNI) is approximately achieved RM 53 billion. The most important factor to have good fertilizer management system. In this research, it focusses on comparison on economic and technical analysis for fertilizer mechanization application affecting oil palm production and to investigate the effects of fertilizer mechanization application toward oil palm production. The study has been conducted at Pahang at three different estates which are Penor Makmur, Sri Kruing, and Pulau manis. The methods of data collection system being used in the study is by interviewing and collecting secondary data. The data then being analyzed through benefit cost ratio, partial budgeting and independent sample t-test. The results from this study showed that, by using spreader system for fertilization, higher economic and technical benefits can be achieved by the plantation based on benefits cost ratio analysis and motion study that has been done. It has also proven by the t-test which show that there is a significant difference on the production of oil palm based on mechanization application based on p value ˂ 0.05. As a recommendation, all the oil palm plantation and smallholders should apply spreader mechanization in order to gain higher economic and technical productivity.